Development And Evaluation Of Culture-Based Mhealth User Interface Guidelines For Elderly Arab Users - Sswey, Ahmed Housni Ahmed Al (2019)
Despite the extensive availability of mobile applications in the Arab world, the relationship amongst its culture, mobile user interface (UI) elements and elderly Arab people has not been thoroughly explored. Moreover, the Arab world lacks usability guideline to support usable and effective mobile app UI design, which has resulted in low acceptance and satisfaction. This study involved the development and evaluation of culture-based UI guidelines and mobile applications for elderly Arab users. A preliminary study involving 40 elderly Arab users was carried out to (i) identify the usable elements of mobile UI and the current problems they encountered when using mobile apps, and to (ii) investigate their suggestions regarding the cultural values of these UI elements. From the preliminary work, ten UI elements and six problems encountered by them were identified. Then, these UI elements and problems were mapped, and all the possible combinations of UI components, cultural aspects and usability components were analysed in drafting a guideline. The final guideline was grouped into five distinct categories involving 40 UI design guidelines and 26 guidelines for the problems encountered by elderly Arab users when using mobile apps. Rapid Development Model together with the Unified Modelling Language was then applied to design and develop a mobile health (mHealth) app based on the guidelines.